Collection of Oral Fluids Using Cotton Ropes as a Sampling Method to Detect Foot‐and‐Mouth Disease Virus Infection in Pigs. Issue 5 (11th December 2013) - Vosloo, W.; Morris, J.; Davis, A.; Giles, M.; Wang, J.; Nguyen, H. T. T.; Kim, P. V.; Quach, N. V.; Le, P. T. T.; Nguyen, P.H.N.; Dang, H.; Tran, H. X.; et al.
Summary In high‐density farming practices, it is important to constantly monitor for infectious diseases, especially diseases that have the potential to spread rapidly between holdings. Pigs are known to amplify foot‐and‐mouth disease (FMD) by excreting large amounts of virus, and it is therefore important to detect the virus quickly and accurately to minimize the spread of disease. Ropes were used to collect oral fluid samples from pigs, and each sample was compared to saliva samples collected from individual animals by detecting FMD virus RNA using real‐time PCR. Two different experiments are described where groups of pigs were infected with different serotypes of FMD virus, either with or without vaccination, and unvaccinated pigs were kept in aerosol contact. The sensitivity of the rope sampling varied between 0.67 and 0.92, and the statistical agreement between this method and individual sampling ranged from substantial to moderate for the two different serotypes. The ease of collecting oral fluids using ropes together with the high sensitivity of subsequent FMD detection through PCR indicates that this could be a useful method to monitor pig populations for FMD virus infection. With further validation of the sensitivity of detection of FMD virus RNA, this can be a cost‐effective, non‐invasive diagnostic tool.